Propuesta del manual de procesos y procedimientos para el departamento de catastro y rentas del Gobierno Autónomo Descentralizado Cantón Bolívar. - Cedeño Zambrano, Hilda Carolina (2016)
This research aims to contribute with a tool that systematically groups the undertaken activities in the department of Land and Rents of the Decentralized Self-government in the canton of Bolívar. To carry out the purpose an interview was addressed to the respective public workers of the department, same that allowed direct contact and discuss the problem concerning the lack of a guide. Therefore, the proposal for a manual of processes and procedures that define the roles and responsibilities in compliance with the quickly performance and efficiency was determined. Furthermore that contributes to reduce waste of time in the administrative management as well as to achieve standardize the same; likewise the activities and tasks are graphically presented to be developed in order to facilitate the identification of processes with a common language, adding value to the public service. Thus factors were charted as: the identification of processes, analysis of activities and finally the design of the manual to meet the changes of the organizational environment. The inductive methods were applied, which allows to observe directly the causes that generated the problem; and deductive for the description and analysis of the collected information. Also there were used conceptualizations that allowed to structure the theoretical base – rules. Through the obtained results it is concluded that the manual seeks to optimize resources expediting the registration of taxes that are paid by the community.